Analysis of Occupational Safety Implementation on Pipeline Work on Ships - Upa Randan Tandirerung; K.P. Suharyono S. Hadiningrat; Verry Albert Jekson Mardame Silalahi (Jurnal Cakrawala Akademika, 2025)
Occupational safety in the maritime industry, particularly in pipeline work on ships, is critical given the risks faced due to harsh working conditions and an uncertain environment. This study uses a qualitative descriptive approach to identify and analyze the safety practices implemented, including effective mitigation measures such as hazardous material replacement and the application of monitoring technologies. The results show that systematic risk identification and active involvement of workers in the safety process are key to building a strong safety culture. However, the challenges faced, such as environmental conditions and diverse worker backgrounds, can hinder the implementation of safety procedures. The conclusions of this study emphasize the importance of management's commitment to safety practices and the need for continuous evaluation and updating of procedures. Suggestions for further research include the development of a more structured training program and the exploration of the use of modern technology in safety management. Thus, investment in safety technology and proper training can improve the effectiveness of occupational safety and reduce the risk of accidents in the maritime industry.